DESIGN AND ANALYSIS OF POTENTIAL LATERAL BUCKLING FAILURE ON OFFSHORE PIPELINE IN JAVA SEA - Savitri Andriani, Miranda
Pipeline is a solution that is considered more efficient than tanker tanks in the transportation of any product if the transportation distance is relatively close. Pipelines at offshore locations experience many environmental loads in the form of currents and waves. The design process needs to be carried out under operating, hydrotest, and installation conditions with a pipe wall design configuration using the DNV-OS-F101 standard, design on the seabed using the DNV-RP-F109 standard, installation analysis based on DNVGL-ST-F101, and free span design using the DNV-RP-F105 standard. After that, the pipe laying configuration was designed based on the thermal expansion analysis using the ASME B31.8 Ch VIII standard. Then the analysis of the potential for lateral buckling failure was carried out using the Hobbs method. Based on the design process carried out in this Final Project, the wall thickness of the pipe that will be used is 12.7 mm (0.5 in), the required concrete layer thickness is 40 mm (1.5748 in). Then, the free span of the pipe is 20 m. In the thermal expansion analysis, it was found that the pipe will elongate by 74.25 mm during hydrotest conditions and by 74.50 mm during operating conditions. The results of the further analysis carried out stated that the pipe that has been determined is unlikely to experience lateral buckling failure because the axial is not large enough to trigger failure.